2012
DOI: 10.1038/tp.2011.63
|View full text |Cite
|
Sign up to set email alerts
|

Plasma biomarkers of depressive symptoms in older adults

Abstract: The pathophysiology of negative affect states in older adults is complex, and a host of central nervous system and peripheral systemic mechanisms may play primary or contributing roles. We conducted an unbiased analysis of 146 plasma analytes in a multiplex biochemical biomarker study in relation to number of depressive symptoms endorsed by 566 participants in the Alzheimer's Disease Neuroimaging Initiative (ADNI) at their baseline and 1-year assessments. Analytes that were most highly associated with depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 77 publications
(96 reference statements)
1
62
0
Order By: Relevance
“…These findings highlight the potential utility of biomarker tests that capture molecular profiles, which can ultimately help stratify individuals based on their susceptibility to develop depression. The insulin finding also confirms the results from other studies showing an increase in depression patients [24,77] and association with depression severity [78] as well as insulin resistance in depression [79,80]. The role of GH in depression is supported by studies showing that individuals with GH deficiency have higher rates of depression, and GH replacement therapy improves depression symptoms, although findings are inconsistent [81,82,83].…”
Section: Discussionsupporting
confidence: 80%
“…These findings highlight the potential utility of biomarker tests that capture molecular profiles, which can ultimately help stratify individuals based on their susceptibility to develop depression. The insulin finding also confirms the results from other studies showing an increase in depression patients [24,77] and association with depression severity [78] as well as insulin resistance in depression [79,80]. The role of GH in depression is supported by studies showing that individuals with GH deficiency have higher rates of depression, and GH replacement therapy improves depression symptoms, although findings are inconsistent [81,82,83].…”
Section: Discussionsupporting
confidence: 80%
“…Several studies of subjects with late-life depression report a deficiency of neurotrophins, including nerve growth factor, glial-derived neurotrophic factor, and brain-derived neurotrophic factor (Diniz et al 2012(Diniz et al , 2013Erickson et al 2012). Arnold et al (2012) examined the cohort from the Alzheimer's Disease Neuroimaging study, comprising individuals affected with subsyndromal depressive symptoms and whose cognitive status ranged from normal to MCI to mild AD. Interestingly, they found that vascular endothelial growth factor (involved in angiogenesis and neurogenesis) and hepatocyte growth factor (involved in long-term potentiation and response to ischemic injury) were increased in older patients with depressive symptoms.…”
Section: Neurotrophinsmentioning
confidence: 99%
“…Testing blood with a panel of systemic inflammation markers revealed a linear or prospective relationship between depressive symptoms and levels of IL-6 and IL-8, respectively, in the elderly [48]. Another study in elderly MDD patients employed a multiplex panel previously developed on the Luminex platform to measure proteins from the cancer, cardiovascular disease, metabolic disorders, inflammation, and Alzheimer's disease literature [49]. Analytes that were most highly associated with depressive symptoms included hepatocyte growth factor, insulin polypeptides, pregnancy-associated plasma protein-A, and vascular endothelial growth factor.…”
Section: Protein Markersmentioning
confidence: 98%
“…An alternate, unbiased process integrates genome-wide expression and genetic findings to identify biomarkers [39]. Candidate biomarker analyses, on the other hand, are motivated by either the results of prior literature [57][58][59] or the availability of a panel of markers with nonspecific purposes [38,49,60]. An explanation of terminology commonly used in the discussion of biomarkers will help hone in on the definition of a biomarker and interpret Fig.…”
Section: Criteria For a Clinically Relevant Biomarker For Depressionmentioning
confidence: 99%